Surface ozone-temperature relationships in the eastern US: A monthly climatology for evaluating chemistry-climate models - Rasmussen, D.J.; Fiore, A.M.; Naik, V.; Horowitz, L.W.; McGinnis, S.J.; Schultz, M.G. (Atmospheric environment (1994), 2012)
We use long-term, coincident O 3 and temperature measurements at the regionally representative US Environmental Protection Agency Clean Air Status and Trends Network (CASTNet) over the eastern US from 1988 through 2009 to characterize the surface O 3 response to year-to-year fluctuations in weather, for the purpose of evaluating global chemistry-climate models. We first produce a monthly climatology for each site over all available years, defined as the slope of the best-fit line ( m O3-T) between monthly average values of maximum daily 8-hour average (MDA8) O 3 and monthly average values of daily maximum surface temperature ( T max). Applying two distinct statistical approaches to aggregate the site-specific measurements to the regional scale, we find that summer time m O3-T is 3–6 ppb K −1 ( r = 0.5–0.8) over the Northeast, 3–4 ppb K −1 ( r = 0.5–0.9) over the Great Lakes, and 3–6 ppb K −1 ( r = 0.2–0.8) over the Mid-Atlantic. The Geophysical Fluid Dynamics Laboratory (GFDL) Atmospheric Model version 3 (AM3) global chemistry-climate model generally captures the seasonal variations in correlation coefficients and m O3-T despite biases in both monthly mean summertime MDA8 O 3 (up to +10 to +30 ppb) and daily T max (up to +5 K) over the eastern US. During summer, GFDL AM3 reproduces m O3-T over the Northeast ( m O3-T = 2–6 ppb K −1; r = 0.6–0.9), but underestimates m O3-T by 4 ppb K −1 over the Mid-Atlantic, in part due to excessively warm temperatures above which O 3 production saturates in the model. Combining T max biases in GFDL AM3 with an observation-based m O3-T estimate of 3 ppb K −1implies that temperature biases could explain up to 5–15 ppb of the MDA8 O 3 bias in August and September though correcting for excessively cool temperatures would worsen the O 3 bias in June. We underscore the need for long-term, coincident measurements of air pollution and meteorological variables to develop process-level constraints for evaluating chemistry-climate models used to project air quality responses to climate change. ► We construct records of O 3-temperature relationships over the eastern US. ► Observed O 3-temperature relationships are used to evaluate a chemistry climate model. ► The model reproduces observed summer O 3 sensitivity to temperature over the Northeast. ► We find modeled temperature biases to partially explain excess-modeled summer O 3. ► Lasting long-term measurements are needed to support process-oriented model evaluation.